Ionospheric electron density and Te/Ti estimation using incoherent scatter power data collected at ALTAIR - Milla, Marco (2006)
The main concern of this thesis is the estimation of ionospheric parameters from incoherent scatter (IS) power data collected with the ALTAIR radar. The estimation is performed using a radar calibration and inversion technique based on a forward model of the scattered power. The model considers the physics of the ionosphere in terms of IS radar cross section (RCS) of the medium. The inversion procedure provides the estimates of plasma density and electron-ion temperature ratio (Te/Ti) of the probed ionosphere.